Development and Validation of a Nomogram for Preoperative Prediction of Lymph Node Metastasis in Lung Adenocarcinoma Based on Radiomics Signature and Deep Learning Signature - Ran, Jia; Cao, Ran; Cai, Jiumei; Yu, Tao; Zhao, Dan; Wang, Zhongliang (Frontiers in Oncology, 2021)
Background and Purpose: The preoperative lymph node (LN) status of patients with lung adenocarcinoma (LUAD) is a key factor for determining if systemic nodal dissection is required, which is usually confirmed after surgery. This study aimed to develop and validate a nomogram for preoperative prediction of LN metastasis in LUAD based on a radiomics signature and deep learning signature. Materials and Methods: This retrospective study included a training cohort of 200 patients, an internal validation cohort of 40 patients, and an external validation cohort of 60 patients. Radiomics features were extracted from conventional computed tomography (CT) images. T-test and extra-trees were performed for feature selection, and the selected features were combined using logistic regression to build the radiomics signature. The features and weights of the last fully connected layer of a convolutional neural network (CNN) were combined to obtain a deep learning signature. By incorporating clinical risk factors, the prediction model was developed using a multivariable logistic regression analysis, based on which the nomogram was developed. The calibration, discrimination and clinical values of the nomogram were evaluated. Results: Multivariate logistic regression analysis showed that the radiomics signature, deep learning signature, and CT-reported LN status were independent predictors. The prediction model developed by all the independent predictors showed good discrimination (C-index, 0.820; 95% CI, 0.762 to 0.879) and calibration (Hosmer-Lemeshow test, p=0.193) capabilities for the training cohort. Additionally, the model achieved satisfactory discrimination (C-index, 0.861; 95% CI, 0.769 to 0.954) and calibration (Hosmer-Lemeshow test, p=0.775) when applied to the external validation cohort. An analysis of the decision curve showed that the nomogram had potential for clinical application. Conclusions: This study presents a prediction model using a radiomics signature, deep learning signature, and CT-reported LN status, that can be used to predict preoperative LN metastasis in patients with LUAD.